Extraordinary Thermal Stability of an Oligodeoxynucleotide Octamer Constructed from Alternating 7‐Deaza‐7‐iodo guanine and 5‐Iodocytosine Base Pairs – DNA Duplex Stabilization by Halogen Bonds?. Issue 4 (April 2014) - Ramzaeva, Natalya; Eickmeier, Henning; Rosemeyer, Helmut
Abstract A reinvestigation of the published X‐ray crystal‐structure analyses of 7‐halogenated (Br, I) 8‐aza‐7‐deaza‐2′‐deoxyguanosines Br7c7z8Gd; 1a and I7c7z8Gd, 1b, as well as of the structurally related 7‐deaza‐7‐iodo‐2′‐deoxy‐β‐D‐ribofuranosyladenine (β‐I7c7Ad; 2=6e in Table 1) and its α‐D‐anomer (α‐I7c7Ad; 3) clearly revealed the existence of halogen bonds between corresponding halogen substituents and the adjacent N(3)‐atoms of neighboring nucleoside molecules within the single crystals. These halogen bonds can be rationalized by the presence of a region of positive electrostatic potential, the σ‐hole, on the outermost portion the halogen's surface, while the three unshared pairs of electrons produce a belt of negative electrostatic potential around the central part of the halogen substituent. The N(3) atoms of the halogenated nucleosides carry a partial negative charge. This novel type of bonding between nucleosides was tentatively used to explain the extraordinary high stability of oligodeoxynucleotides constructed from halogenated nucleotide building blocks.